PENERAPAN METODE BRAINSTORMING DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS XII DI SMA YP PGRI 2 MAKASSAR - Saverius Sudarman; Muh. Yunus; Andi Fatmayanti (STKIP Pembangunan Indonesia Makassar, 2020)
This study aims to determine the application of brainstorming methods in improvingstudent learning outcomes in class XII at YP PGRI 2 Makassar High School. This researchuses classroom action research methods. The subjects of the study were 30th grade studentsof YP PGRI 2 Makassar High School. Data collection tools used are tests, observations anddocumentation. The data obtained were analyzed using qualitative data techniquesinteractive models from Miles and Huberman consisting of data reduction, data presentationand verification and conclusions. The results showed the learning outcomes of class XIIstudents at SMA YP PGRI 2 Makassar increased from cycle I with an average value of 74.16to 81.16 in cycle II. It was concluded that the brainstorming learning method can improve thelearning outcomes of class XII students at YP PGRI 2 Makassar High School.Keywods: Brainstorming Method, Learning Outcomes